Effectiveness of Spinal Flexibility Exercises on Balance in Parkinsonism - Nigave, Chaitali Rajendra; Jagtap, Vaishali (Journal of Neonatal Surgery, 2025)
Background: Parkinsonism is a neurodegenerative disorder characterized by motor symptoms such as tremors, rigidity, bradykinesia, and postural instability, leading to significant impairments in balance and mobility. Spinal flexibility plays a crucial role in maintaining posture and stability, and reduced flexibility is often observed in individuals with Parkinsonism. Limited spinal mobility may contribute to balance issues and an increased risk of falls in these patients. Spinal flexibility exercises, targeting the improvement of trunk and spinal mobility, have shown promise in enhancing posture and balance. This study aims to evaluate the effectiveness of spinal flexibility exercises in improving balance in individuals with Parkinsonism, potentially offering a simple, accessible intervention to mitigate balance-related challenges associated with the condition. Methods: This randomized clinical trial will assess the impact of an intervention on balance in individuals with Parkinsonism. Thirty participants, diagnosed with stage 1 or 2 Parkinsonism, will be selected via random sampling. Inclusion criteria include the ability to follow instructions, willingness to consent, and a history of balance issues or falls. Exclusions include neurological, orthopedic, or cardiopulmonary disorders, cognitive impairments, recent medication changes, or psychiatric conditions. The primary outcome is the Berg Balance Scale (BBS). Participants will undergo a six-week intervention, with data analyzed post-assessment. Ethical approval and informed consent will be obtained. Result: Based on the statistical analysis, the effectiveness of spinal flexibility exercises on balance in Parkinsonism was considered highly significant (p<0.0001). Conclusion: Spinal flexibility exercises serve as a valuable intervention for improving balance and reducing fall risk in individuals with Parkinsonism. Proprioception, movement coordination, and postural control are all improved by these exercises, which raises functional mobility and general quality of life. While more research is needed to develop standardized procedures and evaluate long-term effectiveness, the evidence currently available supports the inclusion of spinal flexibility exercises in rehabilitation programs for Parkinsonism. Personalized rehabilitation techniques and exercise technology advancements may enhance and maximize their efficacy, ultimately leading to better patient outcomes in the treatment of Parkinson's disease.